The Implementation of MPU Aceh Fatwa Number 02 of 2015 on Divorce: Perspectives of MPU Aceh Tamiang and Judges of Mahkamah Syar'iyah Kuala Simpang - Hakim, Lukmanul (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
Divorce can only be carried out based on a judge's decision in an Islamic Court session (Article 115 of the Compilation of Islamic Law). However, in practice, many divorces occur outside of court, creating confusion in society. This is particularly challenging for the Acehnese community, which follows the Shafi’i school of thought, as they are required to abide by laws that do not always align with religious edicts. The fatwas issued by the Aceh Consultative Assembly (MPU), for instance, often conflict with rulings from the Mahkamah Syar'iyah on matters such as the validity of triple talaq pronounced in a single instance. The research questions in this study are: 1) What is the opinion of MPU Aceh Tamiang on the implementation of MPU Aceh Fatwa Number 02 of 2015 on Talaq? 2) What is the perspective of judges at the Mahkamah Syar’iyah Kuala Simpang on the implementation of MPU Aceh Fatwa Number 02 of 2015 on Talaq in court rulings? This research is a Comparative Law Study using both comparative and sociological or philosophical approaches. The research findings indicate that: 1) MPU Aceh Tamiang supports the implementation of the MPU Aceh Fatwa by referring to Qanun Aceh Number 2 of 2009 concerning MPU, which mandates that district/city MPUs are responsible for upholding MPU Aceh’s fatwas. 2) Judges at the Mahkamah Syar’iyah Kuala Simpang acknowledge MPU’s authority to issue fatwas based on legal mandate. However, the implementation of MPU Aceh Fatwa Number 02 of 2015 on Talaq cannot serve as a legal basis for judges in Mahkamah Syar’iyah decisions, as fatwas are not part of the legal hierarchy. For a fatwa to be considered as a source of legal reasoning, it must be codified as a Qanun (regional regulation) in Aceh.